The Influence of Online Media on Islamic Education Values among Students of the Islamic Education Study Program in Sekolah Tinggi Agama Islam (STAI) Al-Furqan Makassar - Siti Hartina; Juhasdi Susono; Aryandi Sudika; Rosika Indri Karadona (Edusoshum : Journal of Islamic Education and Social Humanities, 2025)
The main focus of this research is to analyze the extent of the influence of online media on Islamic educational values among Sekolah Tinggi Agama Islam (STAI) Al-Furqan Makassar students. The background of this research is the high intensity of online media usage by students of the Sekolah Tinggi Agama Islam (STAI) Al-Furqan Makassar, but not all of them exhibit attitudes or behaviors that reflect the values of Islamic education. This research uses a quantitative approach with a survey method and an ex post facto design. The research sample consists of 45 students from the Islamic Education Study Program at the Sekolah Tinggi Agama Islam (STAI) Al-Furqan Makassar. The data collection instrument used a questionnaire with indicators on the online media variable: intensity, usefulness, and effectiveness. Indicators of the variable Islamic education values: aqidah, akhlak, and sharia. This study uses ordinal regression analysis to process the obtained data, as the data is not normally distributed. The analysis results show that online media significantly influences Islamic education values, as indicated by a significance value of < 0.001 in the Model Fitting Information and Parameter Estimates. The Nagelkerke R Square value of 0.332 indicates that online media contributes 33.2% to the formation of Islamic education values, while the remaining 66.8% is influenced by other unexamined variables. Therefore, it can be concluded that online media has a quite strong and significant influence on the values of Islamic education among students of the Islamic Education Study Program at the Sekolah Tinggi Agama Islam (STAI) Al-Furqan Makassar.